Discrimination due to Ethnicity and Gender: How susceptible are video-based job interviews? - Esther Kroll; Matthias Ziegler (International Journal of Selection and Assessment, 2016)
Fairness toward job applicants differing in gender and ethnicity in a video-based assessment interview was explored. For this purpose, 103 female and 105 male participants, including 38 who declared to have a migration background of their own, rated a behavior anchored rating scale after having watched the videotaped answers of a potential applicant. The domains assessed were communication skills and the capacity to work in a team. The videos of the applicants were generated with the help of standardized scripts and semi-professional actors. Eight videos were made operationalizing a two (Turkish migration background–native German) by two (male–female) by two (more positive applicant answers–moderately good applicant answers) experimental design. A multivariate analysis of variance (MANOVA) revealed a small to moderate main effect only for migration background of the applicants. Subsequent ANOVAs found that in three of the four dependent variables this effect reached significance of p0.167em<0.167em.05. The effects were robust against consideration of the raters' agreeableness and the raters' own migration background as covariates. Applicants with Turkish background scored higher in the evaluation of their videotaped answers than German native applicants did. Social Identity Theory (Taijfel & Turner, 1986) provides an approach to integrate these findings.
Keywords: 330